2021
DOI: 10.3390/foods10030549
|View full text |Cite
|
Sign up to set email alerts
|

Pea Protein Extraction Assisted by Lactic Fermentation: Impact on Protein Profile and Thermal Properties

Abstract: Although pea protein has been widely explored, its consumption is still limited by undesirable sensory characteristics and low solubility. All these properties can be modified during protein extraction process. Besides, previous studies showed that lactic acid bacteria (LAB) have a positive effect on legume protein ingredients in terms of flavor and functional properties. Hence, the objective of this work was to explore an alternative extraction method based on alkaline extraction/isoelectric precipitation (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…In another study, the combination of different lactic acid bacteria ( Lactobacillus acidophilus , Streptococcus thermophilus , and Bifidobacterium lactis ) was used to study the effect of fermentation on pea protein extraction. The results showed that due to the fermentation, the protein content and yield of albumin rich fraction were increased about 20% and 30%, respectively (Emkani et al, 2021). This is the first time that SSF of HDRB with the highest amount of soluble protein is reported.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the combination of different lactic acid bacteria ( Lactobacillus acidophilus , Streptococcus thermophilus , and Bifidobacterium lactis ) was used to study the effect of fermentation on pea protein extraction. The results showed that due to the fermentation, the protein content and yield of albumin rich fraction were increased about 20% and 30%, respectively (Emkani et al, 2021). This is the first time that SSF of HDRB with the highest amount of soluble protein is reported.…”
Section: Resultsmentioning
confidence: 99%
“…It is not completely clear how whole Euglnea cell powder was able to elicit the Lactobacillus growth. Lactic acid bacteria are known to be proteolytic ( Emkani et al., 2021 ), responsible for protein aggregation ( Berterame et al., 2016 ) and thus act as a permeabilizer and outer membrane-disintegrating agent ( Alakomi et al., 2000 ) due to lactic acid production. Therefore, it can be hypothesized that Euglena which only has a proteinaceous pellicle membrane as outer covering might be more susceptible to leakage leading to paramylon and other cellular components release which might have aided in the Lactobacilus growth.…”
Section: Resultsmentioning
confidence: 99%
“…More work is needed to integrate these findings into commercial processes. Some other new ideas involve using fermentation to assist protein extraction [68] or redesigning the wet fractionation process to be milder [69]. Some authors even suggest to selectively extract the albumin fraction (under acidic conditions) to obtain a functional protein isolate while using the residual proteins for feed [70].…”
Section: Plant Protein Fractionationmentioning
confidence: 99%